Kinetic analysis of ski turns based on measured ground reaction forces - Vaverka, F.; Vodickova, S.; Elfmark, M. (Journal of Applied Biomechanics, 2012)
The objective of this study was to devise a method of kinetic analysis of the ground reaction force that enables the durations and magnitudes of forces acting during the individual phases of ski turns to be described exactly. The method is based on a theoretical analysis of physical forces acting during the ski turn. Two elementary phases were defined: (1) preparing to turn (initiation) and (2) actual turning, during which the center of gravity of the skier-ski system moves along a curvilinear trajectory (steering). The starting point of the turn analysis is a dynamometric record of the resultant acting ground reaction force applied perpendicularly on the ski surface. The method was applied to six expert skiers. They completed a slalom course comprising five gates arranged on the fall line of a 26° slope at a competition speed using symmetrical carving turns (30 evaluated turns). A dynamometric measurement system was placed on the carving skis (168 cm long, radius 16 m, data were recorded at 100 Hz). MATLAB procedures were used to evaluate eight variables during each turn: five time variables and three force variables. Comparison of the turn analysis results between individuals showed that the method is useful for answering various research questions associated with ski turns.